Perceived impacts of company Workplace Health Promotion on employment relationship - Fehér, János; Reich, Matthias (Journal of Eastern European and Central Asian Research (JEECAR), 2020)
Workplace Health Promotion (WHP) as part of Workplace Health Management (WHM) is an emerging function within organizational HRM. Research has investigated the economic feasibility of WHM by examining health-related productivity losses and presenteeism but has also shown connections of WHM and employee reactions, i. a. happiness, confidence, job satisfaction, and perceptions of being cared for by employers. The goal of this paper is to examine possible impacts of WHM, and especially WHP on certain motivational and emotional aspects of the employment relationship, namely the perceived attractiveness of the employer, and perceived impacts of WHM/WHP on emotional atmosphere, work motivation, commitment of the employees, and the number of voluntary quits.